Metals from human activities in a coastal Lagoon Saltmarsh - Sediment toxicity and phytoremediation by Sarcocornia fruticosa - Silva, Manuela (2021)
Anthropogenic pressure on coastal areas has been increasing in the last decades, threating the saltmarshes and the ecosystem services they provide. Sarcocornia fruticosa can have an important role in sequestration of metals from human activities. This study evaluated the effect of metal toxicity in saltmarsh sediment (measured by Ecological Risk Index-ERI) on S. fruticosa ability to metal (Cd, Cr, Ni, Pb and Zn) remediation (Enrichment Factor and metal translocation). The impact of urbanization was studied through the metal loads on stormwaters during two main rainfall events, and the industrial impact was assessed through data analyses in a saltmarsh area influenced by a stream that receives industrial runoffs. The S. fruticosa response on metal remediation was affected by ERI. In more polluted locations, retained metals on roots and prevented the most toxic (Cd and Pb) from reaching the aerial organs, avoiding tissues death and metal remobilisation to the saltmarsh. Meanwhile, in rhizosediments with conditions to high metal bioavailability, S. fruticosa transported Cd and Pb to aerial organs, but used the Zn translocation to decrease their toxicity. This halophyte resilience is important to saltmarsh metal sequestration in high toxicity conditions, and allows the maintenance of other ecosystem services, contributing to the environmental protection and public health.